Evaluation of quality measurement of Olomouc cake of cheese (Olomoucké tvarůžky) during ripening - Daniela Strnadová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2012)
Olomouc cake of cheese (Olomoucké tvarůžky) is smear-ripened cheese, which is produced from sour industrial curd. Brevibacterium linens, which are added during the production process, are reproducing and make gold-yellow smear cover. The aim of this work was to assess the chemical analysis of the quality of Olomouc cake of cheese. Changes in chemical composition were evaluated during different stages of production and at the same time it was detected whether changes in chemical composition during the manufacturing process are same in spring as well as in summer, without statistically significant differences. Dry matter of Olomouc cake of cheese was ranged from 35 % to 39 %. The increase of dry matter during production is evident, but these changes were in the most cases not statistically signifiant (P > 0.05). The value of titratable acidity of the cheese considerably changes during the manufacturing process, it has a decreasing tendency. Titratable acidity of cheese after shaping was 106.64 (136.12) SH and at the end of life it was 49.91 (65.06) SH. These changes were very highly statistically significant (P 0.05) in cheese from summer period. Content of salt is increased from 5.30 % to 5.98 %, respectively 6.10 %. In spring period the oposite changes in most cases occured (P 0.05).